The amateur geologist : explorations and investigations - Wiggers, Ray. (New York : Franklin Watts, 1993)
Presents projects and activities that explore many aspects of the science of geology.
Includes bibliographical reference (p. 137-138) and index.
Keywords: Geology -- Juvenile literature; Geology; Science projects